2022
DOI: 10.1097/ju.0000000000002534.08
|View full text |Cite
|
Sign up to set email alerts
|

Mp12-08 outcomes of Nephrectomy for Renal Cell Carcinoma With Venous Thrombus Following Immune Checkpoint Inhibitor Therapy: A Multicenter Collaborative Study

Abstract: location. Hilar and retrocaval suspicious lymphadenopathies are associated with higher concordance and increased risk of LNI. In consequence, performing a more extended LND for staging purposes in these patients may allow for a better risk classification and for a better planning of adjuvant treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Reimers et al also cautioned the increased need for time and skill due to the operative challenge and substantial fibrosis in most of the cases. Subsequent larger case series confirmed the feasibility and safety of post-ICI nephrectomy in both open and minimally invasive settings. Gross et al recently reported a large series of 232 patients undergoing CN in the ICI era, 30 of whom received deferred CN; 90% were favorable or intermediate risk and 70% received ICI as a third line or greater treatment, yet no data on perioperative findings or AEs in this subgroup were reported.…”
Section: Discussion and Observationsmentioning
confidence: 80%
See 2 more Smart Citations
“…Reimers et al also cautioned the increased need for time and skill due to the operative challenge and substantial fibrosis in most of the cases. Subsequent larger case series confirmed the feasibility and safety of post-ICI nephrectomy in both open and minimally invasive settings. Gross et al recently reported a large series of 232 patients undergoing CN in the ICI era, 30 of whom received deferred CN; 90% were favorable or intermediate risk and 70% received ICI as a third line or greater treatment, yet no data on perioperative findings or AEs in this subgroup were reported.…”
Section: Discussion and Observationsmentioning
confidence: 80%
“…In addition, retrospective studies on deferred CN after ICI showed that the decision of CN was mainly made at the surgeon’s discretion. Nevertheless, patients with favorable or intermediate risk who responded well to the up-front ICI were more likely to undergo CN …”
Section: Discussion and Observationsmentioning
confidence: 99%
See 1 more Smart Citation